Key intermediates of catalytic reactions with norbornadiene participation - E. M. Evstigneeva; R. S. Shamsiev; V. R. Flid (Тонкие химические технологии, 2006)
Review covers catalytic reactions for which key intermediates – complexes of Mo, Ni and Pd with norbornene derivatives – were isolated. By the example of cyclodimerization of NBD, search of such intermediates by methods of quantum chemistry is described.